A behavioral New Keynesian model of a small open economy under limited foresight - Seunghoon Na; Yinxi Xie (Bank of Canada, 2023)
This paper investigates exchange rate dynamics in open economies by incorporating bounded rationality. We develop a small open-economy New Keynesian model with an incomplete asset market, wherein decision-makers possess limited foresight and can plan for only a finite distance into the future. The equilibrium dynamics depend on the degree of foresight and the decision-makers' belief-updating behaviors that approximate continuation values at the end of their planning horizons. The limited foresight leads to dynamic overshooting of forecast errors in the real exchange rate across different time horizons, while also differentiating the term structure of expectations. This framework hence provides a micro-foundation for understanding time and forecast horizon variability in uncovered interest parity (UIP) puzzles.
Keywords: E43; E70; F31; F41; 330; Exchange rates; Monetary policy transmission; International topics; Business fluctuationsand cycles